(untitled) (Journal of Applied Learning and Teaching, 2025)
Education has been considered an elevator that allows people to progress socially. Unfortunately, this is not always the case, so it is essential that teachers understand the influence that poverty has on the development of students who live in this condition. This is why the aim of this study is to analyse future teachers’ perceptions of the relationship between poverty and education. To this end, qualitative phenomenological research was conducted using the collective case study method. A sample of 127 students from the Master in Teacher Training at Spanish universities was exposed to life experiences and readings from the Report of the Special Rapporteur on extreme poverty and human rights, which was presented at the United Nations Human Rights Council for Spain in 2020. Individual written reflections and group discussions were conducted. The results showed that this type of experience helps to eliminate teachers’ prejudices and stereotypes about students and their families who unfortunately live in socioeconomically disadvantaged conditions, as well as promoting a consciousness of equity and educational social justice.